Effect of sunlight and temperature on winter agricultural production of wheat and barley in Said Sadiq district - Ahmed, Roshna Amin Ahmed; Ahmad, Prof.Dr.Soran Hama Amin Ahmad (Sulaimani Journal for Humanities, 2025)
This research is entitled (The Effect of Sunlight and Temperature on Winter Crops (Wheat and Barley) in the Said Sadiq District). Climate is one of the main factors influencing human activities, especially agricultural practices. Among the various climatic elements, sunlight and temperature play a crucial role in determining the yield of winter crops (wheat and barley). There are also notable variations in sunlight and temperature depending on the month and year. In this context, local climate conditions are essential for understanding the relationship between these two climatic factors and crop production. Climate helps determine both the quantity and type of agricultural output, as each crop has specific environmental requirements. This study aims to identify the optimal time for planting winter crops (November). To determine the climatic requirements for winter crops, we relied on climate data recorded at the Halabja Meteorological Station from 2009 to 2023. In addition, we used data on the cultivated areas of wheat and barley crops obtained from the (General Directorate of Agriculture in Sulaimani\ Planning and Monitoring Department) for the same period (2009-2023). Our findings indicate that the total sown area in the study region amounted to (74213.3) acres for wheat and (6660) acres for barley as shown in table(9). We employed (Pearson Correlation analysis) to examine the relationship between sunlight and temperature with the yields of wheat and barley. The results showed an inverse relationship between wheat yields with both sunlight and temperature. In contrast, barley yields demonstrated a direct correlation only with the average minimum temperature (r=0.073), while showing an inverse relationship with sunlight, average temperature, and average maximum temperature. Finally, based on these findings, we proposed several suggestions and recommendations to enhance crop productivity in the region
Keywords: Sunlight; temperature; winter agricultural crops (wheat and barley); Said Sadiq district; area and yield